THE IMPLEMENTATION OF ASSERTION, REASON, EVIDENCE AND LINK BACK (AREL) IN TEACHING SPEAKING - Sri Wahyuni; Mulyadi Syahputra; Defi Irmayanti (Getsempena English Education Journal, 2020)
This study analyses the students’ perceptions about the use of Assertion, Reason, Evidence and Link Back in teaching speaking. The population of this research was second grade students of SMAN 4 Banda Aceh which consist of 250 students and only 32 students at class XI IA 2 took as the sample of this research. The instruments of this research was questionnaire. This study was applied qualitative analysis by using percentage formula. The result of this study shows that the students’ perception performance got a positive impact after learning A.R.E.L. Thus, the students have been motivated to speak in front of class and A.R.E.L effect students’ speaking understanding in giving their argument.